Alfvénic Acceleration Sustains Ganymede's Footprint Tail Aurora. Issue 3 (3rd February 2020) - Szalay, J. R.; Allegrini, F.; Bagenal, F.; Bolton, S. J.; Bonfond, B.; Clark, G.; Connerney, J. E. P.; Ebert, R. W.; Gershman, D. J.; Giles, R. S.; Gladstone, G. R.; Greathouse, T.; et al.
Abstract: Integrating simultaneous in situ measurements of magnetic field fluctuations, precipitating electrons, and ultraviolet auroral emissions, we find that Alfvénic acceleration mechanisms are responsible for Ganymede's auroral footprint tail. Magnetic field perturbations exhibit enhanced Alfvénic activity with Poynting fluxes of 100 mW/m 2 . These perturbations are capable of accelerating the observed broadband electrons with precipitating fluxes of 11 mW/m 2, such that Alfvénic power is transferred to electron acceleration with 10% efficiency. The ultraviolet emissions are consistent with in situ electron measurements, indicating 13 ± 3 mW/m 2 of precipitating electron flux. Juno crosses flux tubes with both upward and downward currents connected to the auroral tail exhibiting small‐scale structure. We identify an upward electron conic in the downward current region, possibly due to acceleration by inertial Alfvén waves near the Jovian ionosphere. In concert with in situ observations at Io's footprint tail, these results suggest that Alfvénic acceleration processes are broadly applicable to magnetosphere‐satellite interactions. Plain Language Summary: Jupiter's moon Ganymede interacts with the planet's rapidly rotating magnetic field, which generates an aurora in the Jovian upper atmosphere. The Juno spacecraft crossed magnetic field lines connected to this aurora. We found that a specific type of wave, similar to a wave produced when a string is plucked, is responsible for accelerating the electrons sustaining this aurora. This type of interaction between a moon and the planet it orbits is likely a common process occurring at other exoplanetary systems. Key Points: First in situ particles and fields measurements connected to Ganymede's auroral tail are reported Alfvén wave activity is observed with Poynting fluxes of 100 mW/m 2 capable of accelerating electrons into the atmosphere Ganymede's footprint tail contains electron populations consistent with Alfvénic acceleration and precipitating energy fluxes of 11 mW/m 2